In Utero Activation of Natural Killer Cells in Congenital Cytomegalovirus Infection. (25th July 2022) - Vaaben, Anna V; Levan, Justine; Nguyen, Catherine B T; Callaway, Perri C; Prahl, Mary; Warrier, Lakshmi; Nankya, Felistas; Musinguzi, Kenneth; Kakuru, Abel; Muhindo, Mary K; Dorsey, Grant; Kamya, Moses R; et al.
Abstract: Background: Congenital cytomegalovirus (CMV) infection is the most common infectious cause of birth defects and neurological damage in newborns. Despite a well-established role for natural killer (NK) cells in control of CMV infection in older children and adults, it remains unknown whether fetal NK cells can sense and respond to CMV infection acquired in utero. Methods: Here, we investigate the impact of congenital CMV infection on the neonatal NK-cell repertoire by assessing the frequency, phenotype, and functional profile of NK cells in cord blood samples from newborns with congenital CMV and from uninfected controls enrolled in a birth cohort of Ugandan mothers and infants. Results: We find that neonatal NK cells from congenitally CMV infected newborns show increased expression of cytotoxic mediators, signs of maturation and activation, and an expansion of mature CD56 − NK cells, an NK-cell subset associated with chronic viral infections in adults. Activation was particularly prominent in NK cell subsets expressing the Fcγ receptor CD16, indicating a role for antibody-mediated immunity against CMV in utero. Conclusions: These findings demonstrate that NK cells can be activated in utero and suggest that NK cells may be an important component of the fetal and infant immune response against CMV. Clinical Trials Registration: NCT02793622. Abstract : NK cells from cord blood of congenitally CMV-infected newborns show increased expression of cytotoxic mediators, signs of maturation and activation, and an expansion of the CD56-negative subset, suggesting a potential role in the fetal and neonatal defense against CMV.